Sociopaths with high functionality - Pisanty, Valentina (E|C, 2020)
The title of "highly functional sociopaths" seems to fit a variety of serial characters who respond to an idiosyncratic, often questionable, sometimes execrable moral code, yet perfectly suited to the projects they pursue with extraordinary determination.